Digital Adaptation in Islamic Religious Education: A Comparative Case Study of University and Pesantren in Indonesia - Afrizal Galela; Mohammad Asrori; M. Mujab (Abjadia : International Journal of Education, 2026)
Digital transformation presents a dualism of opportunities and challenges for the sustainability of Islamic Religious Education (PAI). This qualitative multiple-case study analyzes technology integration at the Islamic University of Malang (UNISMA) and Sabilurrosyad Islamic Boarding School. Data were gathered through in-depth interviews, observation, and documentation, then analyzed using the Miles, Huberman, and Saldaña interactive model. Findings show that UNISMA integrates technology via Learning Management Systems (LMS) to foster constructivist learning, while Sabilurrosyad adopts digital tools selectively to preserve ta'dib (moral discipline) and traditional values. This study demonstrates that effective PAI digitalization requires a synergy between technological utility and Islamic spirituality. Furthermore, it proposes an integration of the Technology Acceptance Model (TAM) with religious value dimensions and ta'dib principles as a theoretical framework for Islamic educational contexts. Ultimately, digital transformation in PAI must transcend instructional efficiency to actively reinforce the moral and spiritual dimensions of learners.